QS. Al-Hujurat: 13 Sebagai Landasan Pendidikan Moderat dalam Implementasi Kurikulum Merdeka PAI Berbasis Leading Turath di MTs Mambaus Sholihin - Elisa Nafilatun Naja; Muhammad Farih (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The Islamic Religious Education (PAI) in the Kurikulum Merdeka is designed not only to develop cognitive competence, but also to build attitudes of religious moderation and respect for diversity. These values align with the message of QS. Al-Hujurat: 13, which emphasizes human diversity as sunnatullah and the foundation of social ethics. This study aims to describe the implementation of the Kurikulum Merdeka for PAI and to explore the role of turāth (classical Islamic texts) in internalizing values of moderation and tolerance at MTs Mambaus Sholihin, a pesantren-based madrasah with a multicultural student background. This research employs a qualitative approach with a case study design. Data were collected through classroom observation, interviews, and documentation related to PAI instructional practices and institutional policies. The findings indicate that the implementation of the Kurikulum Merdeka at MTs Mambaus Sholihin is carried out contextually by integrating the national curriculum with turath texts as instructional sources. Classical books play a significant role in shaping students’ ethics, character, and mutual respect. The internalization of QS. Al-Hujurat: 13 is reflected in the pesantren culture that emphasizes tolerance practices, conflict prevention, and educational approaches in handling student misconduct. This study concludes that the leading turāth approach strengthens the implementation of the Kurikulum Merdeka PAI in developing religious moderation attitudes within a pesantren-based madrasah environment.   Keywords: Merdeka Curriculum, Islamic Religious Education, Religious Moderation, Turath Texts, QS. Al-Hujurat: 13